Myeloid FoxO1 depletion attenuates hepatic inflammation and prevents nonalcoholic steatohepatitis - Lee, Sojin; Usman, Taofeek O.; Yamauchi, Jun; Chhetri, Goma; Wang, Xingchun; Coudriet, Gina M.; Zhu, Cuiling; Gao, Jingyang; McConnell, Riley; Krantz, Kyler; Rajasundaram, Dhivyaa; Singh, Sucha; et al. (The Journal of clinical investigation, 2022)
Hepatic inflammation is culpable for the evolution of asymptomatic steatosis to nonalcoholic steatohepatitis (NASH). Hepatic inflammation results from abnormal macrophage activation. We found that FoxO1 links overnutrition to hepatic inflammation by regulating macrophage polarization and activation. FoxO1 was upregulated in hepatic macrophages, correlating with hepatic inflammation, steatosis and fibrosis in mice and patients with NASH. Myeloid cell-conditional FoxO1 knockout skewed macrophage polarization from pro-inflammatory M1 to anti-inflammatory M2 phenotypes, accompanied by the reduction of macrophage infiltration in liver. These effects mitigated overnutrition-induced hepatic inflammation and insulin resistance, contributing to improved hepatic metabolism and increased energy expenditure in myeloid cell FoxO1 knockout mice on HFD. When fed a NASH-inducing diet, myeloid cell FoxO1 knockout mice were protected from developing NASH, culminating in the reduction of hepatic inflammation, steatosis and fibrosis. Mechanistically, FoxO1 counteracts Stat6 to skew macrophage polarization from M2 toward M1 signatures to perpetuate hepatic inflammation in NASH. FoxO1 appears as a pivotal mediator of macrophage activation in response to overnutrition and a therapeutic target for ameliorating hepatic inflammation to stem the disease progression from benign steatosis to NASH.